Cost-Effectiveness of Oral Levofloxacin Versus Amoxicillin-Clavulanate/Ciprofloxacin for Outpatient Management of Low-Risk Febrile Neutropenia in Children With Cancer in Egypt - Reham Abdelaziz Khedr; Ebtehal Ali; Zeinab Ahmad Elshafei; Hadir Ahmed El-Mahallawy; Nashwa Ezz Eldeen (JCO Global Oncology)
PURPOSEFebrile neutropenia (FN) is a common cancer complication in children. A growing body of evidence suggests that home-based care with oral antibiotics is safe and effective in carefully selected children with low-risk (LR) FN. This study aimed to assess the efficacy and safety of oral levofloxacin versus oral amoxicillin-clavulanate/ciprofloxacin in the management of LR-FN in children with cancer over a time horizon of 7 days from the National Cancer Institute (NCI) perspective.PATIENTS AND METHODSThis is a randomized controlled study conducted at the NCI from December 2021 to September 2022, including children and adolescents age between 3 and 18 years who presented to the emergency room with LR-FN criteria with the exclusion of patients younger than 3 years and patients with Down syndrome. One hundred LR-FN episodes were enrolled in each arm. Patient demographics, microbiologic data, and outcomes were collected at different time points. A decision analytic model was created to compare the two treatment strategies. The outcome measures included quality-adjusted FN episodes, costs, and incremental cost-effectiveness ratios.RESULTSLevofloxacin was a safe and effective treatment option for LR-FN. It proved to be the dominant strategy against amoxicillin-clavulanate/ciprofloxacin with an incremental quality-adjusted life-year (QALY) of 0.0001 and a lower cost of 62.4996 Egyptian pounds (EGPs) in the treatment of home-based LR-FN with a willingness to pay a threshold of 77,520 EGPs per QALY (1 gross domestic product/capita).CONCLUSIONFor the treatment of FN in pediatric patients with cancer, levofloxacin offers a cost-saving option with improved survival benefits over a 7-day time horizon from the NCI perspective. These findings will help health care decisions regarding the allocation of health care system resources to improve supportive care for patients with LR-FN.